APPLICATION OF TAHFIDZ AL QUR'AN LEARNING METHOD IN IT AL HUDA WONOGIRI HIGH SCHOOL - Nurrahmah Qoyimah; Nurul Latifatul Inayati (Universitas Muhammadiyah Surakarta, 2018)
Learning in memorizing the Qur'an is not only done in boarding school but the learning of memorizing the Qur'an has been applied to the study in schools one of them at SMA IT Al Huda Wonogiri. The curriculum was carried out intensively with the 30-juz memorization target for all students during his education at the Al Huda Wonogiri High School. The research aims to describe how to implement Tahfidz learning methods and identify supporting factors and inhibitors of the application of Tahfidz Al-Qur'an in SMA IT Al Huda Wonogiri. This study used a qualitative descriptive approach with the type of field research (field research) conducted in Al Huda Wonogiri High School with a phenomenological approach. Data collection techniques using observation, documentation and interviews. This research analysis method uses inductive data analysis descriptions.Based on the research conducted, then the researcher can conclude that the method used in the study Tahfidz Al Qur'an is Talaqqi ie to deposit new memory to teachers Tahfizh who have competence in the field of Tahfidz Al-Qur'an, A memorization or a recall of memorization of Tahfidz teachers, Tasmi ' or to listen to memorization to other people, whether individual or group and Murajaah or repeat memorized memory to be sent to Keep from forgetting and wrong. Supporting factors in the application of the Tahfidz method is prioritizing fixing readings rather than memorizing the qualifications of Tahfidz teachers, the mushaf used, determining the memorization target, time and place to memorize and factors of lack of muraja'ah, guidance and time management.